Screens, Streams, and Stress: A Qualitative Study on How Distance Learning Students Cope with Information Overload - Masrek, Mohamad Noorman; Baharuddin, Mohammad Fazli (International Journal of Membrane Science and Technology, 2023)
Extensive research has been conducted in the field of information overload, but little attention has been paid to the experiences of distant learners. This research aims to fill that void by delving into the challenges that distance learning students face in online educational environments. The study addresses the following key issues: How are these students dealing with information overload? What effect does this overload have on their stress and anxiety levels? And, perhaps most importantly, what coping strategies do they employ? Data was gathered through interviews with six distance learners using a general qualitative research methodology. Thematic analysis revealed that these students' information overload stemmed from a variety of sources: excessive course materials, constant notifications, live sessions, and technological challenges, among others. This overload, in turn, manifested as feelings of being overwhelmed, the fear of missing out, digital fatigue, and pressure to perform. However, the study also uncovered resilient coping strategies. Distance learners managed information overload through effective time management, strategic information filtering, mindful digital consumption, active learning techniques, and self-care practices. These findings offer useful insights not only for improving online learning delivery but also for guiding other potential online learners through the challenges of digital education.